Teaching of Cataloguing - Neelameghan, A.; Bhattacharyya, G. (Journal of Information and Knowledge, 1966)
Emphasises that the teaching of cataloguing should be designed in such a way that the knowledge of the theory of catalogue enriches the skill in practical cataloguing and vice versa. Describes a method of developing in the students some practical skills essential for making the formal course productive. Shows the helpfulness of the discussion technique in teaching the theory of cataloguing. Suggests a Rule-Reference Table as an aid for citing the rules in practical cataloguing work. Gives a proforma of the diary form to be used by the student. Mentions the different aspects of teaching to be done in the class and in the tutorial.